Mutant ATRX: uncovering a new therapeutic target for glioma. (3rd July 2018) - Haase, Santiago; Garcia-Fabiani, María Belén; Carney, Stephen; Altshuler, David; Núñez, Felipe J.; Méndez, Flor M.; Núñez, Fernando; Lowenstein, Pedro R.; Castro, Maria G.
ABSTRACT: Introduction : ATRX is a chromatin remodeling protein whose main function is the deposition of the histone variant H3.3. ATRX mutations are widely distributed in glioma, and correlate with alternative lengthening of telomeres (ALT) development, but they also affect other cellular functions related to epigenetic regulation. Areas covered : We discuss the main molecular characteristics of ATRX, from its various functions in normal development to the effects of its loss in ATRX syndrome patients and animal models. We focus on the salient consequences of ATRX mutations in cancer, from a clinical to a molecular point of view, focusing on both adult and pediatric glioma. Finally, we will discuss the therapeutic opportunities future research perspectives. Expert opinion : ATRX is a major component of various essential cellular pathways, exceeding its functions as a histone chaperone (e.g. DNA replication and repair, chromatin higher-order structure regulation, gene transcriptional regulation, etc.). However, it is unclear how the loss of these functions in ATRX-null cancer cells affects cancer development and progression. We anticipate new treatments and clinical approaches will emerge for glioma and other cancer types as mechanistic and molecular studies on ATRX are only just beginning to reveal the many critical functions of this protein in cancer.